2020
DOI: 10.1017/s1751731119003410
|View full text |Cite
|
Sign up to set email alerts
|

Net hepatic release of glucose from precursor supply in ruminants: a meta-analysis

Abstract: For their glucose supply, ruminants are highly dependent on the endogenous synthesis in the liver, but despite the numerous studies that evaluated hepatic glucose production, very few simultaneously measured hepatic glucose production and uptake of all precursors. As a result, the variability of precursor conversion into glucose in the liver is not known. The present study aimed at investigating by meta-analysis the relationships between hepatic glucose net release and uptake of precursors. We used the FLuxes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
0
16
1
4
Order By: Relevance
“…Accordingly, the nonlinear character of the relationship between milk yield and body weight suggest an optimum body weight beyond which the feed-efficiency decreases in specialized breeds [33]. Loncke et al (2020) recently showed a similar pattern for the efficiency of hepatic glucose synthesis (conversion rate of precursors to glucose), which decreases at high levels of precursor supply [34]. As a result, high-producing dairy cows show increased rates of energy mobilization from body tissues to bridge the gap between the supply of energy from feedstuffs and the energy needed to support milk production along with all other energy-demanding life functions [35].…”
Section: Resource Allocation Theorymentioning
confidence: 99%
“…Accordingly, the nonlinear character of the relationship between milk yield and body weight suggest an optimum body weight beyond which the feed-efficiency decreases in specialized breeds [33]. Loncke et al (2020) recently showed a similar pattern for the efficiency of hepatic glucose synthesis (conversion rate of precursors to glucose), which decreases at high levels of precursor supply [34]. As a result, high-producing dairy cows show increased rates of energy mobilization from body tissues to bridge the gap between the supply of energy from feedstuffs and the energy needed to support milk production along with all other energy-demanding life functions [35].…”
Section: Resource Allocation Theorymentioning
confidence: 99%
“…Lower milk and milk protein yields for OS cows compared with ST cows at M4 and a trend for lower milk and milk protein yields at M5 (Figure 4) indicated that the OS-L diet affected milk yield with a delay of approximately 48 h from initial feeding, whereas a lag of about 36 h occurred before milk protein yield was increased (at M7; tendency) on the OS-H diet. A trend for reduced milk lactose yields at M4 and M5 for OS cows may be explained by a reduced metabolizable protein supply with the OS-L diet, resulting in reduced rates of hepatic AA deamination, gluconeogenesis, and lactose synthesis (Daniel et al, 2016;Loncke et al, 2020). This is supported by lower MU at M3 and M4 and higher MU at M6, M7, and M8 for OS cows compared with ST cows (Figure 3).…”
Section: Effects On Milk Yield and Composition By Milkingmentioning
confidence: 92%
“…A systematic study of IF allows one to gain more knowledge from the data. Some examples of this approach can be found in the literature (Loncke et al 2009(Loncke et al , 2015(Loncke et al and 2020Agastin et al 2014). In the meta-analysis of Loncke et al (2015), response equations to predict hepatic uptake/release of ketogenic nutrients in response to their supply to the liver were obtained using published data from the FLORA database (FLuxes of nutrients across Organs and tissues in Ruminant Animals; Vernet and Ortigues-Marty, 2006).…”
Section: Interfering Factorsmentioning
confidence: 99%
“…In this meta-analysis, the study of IF revealed that response equations were significantly affected by other nutrients or by diet characteristics. For example, it was shown that the hepatic release of glucose was related to the net portal appearance of nitrogen (Loncke et al, 2020), but for a same level of nitrogen (LSMeans), the release of glucose increased logically with the dietary starch concentration.…”
Section: Interfering Factorsmentioning
confidence: 99%
See 1 more Smart Citation